2004
DOI: 10.1111/j.1470-6431.2003.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer use of the internet for health information: a survey of primary care patients

Abstract: An increasing number of patients use the internet to obtain information about health. Although some information is available about how health professionals use the internet, little is known about how patients utilize this information. Some patients may actively seek information to assume more responsibility for their health. However, others may feel obliged to do so because of failing confidence in health care provision. Health professionals have the potential to assist patients to make sense of health informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 12 publications
(20 reference statements)
5
52
0
Order By: Relevance
“…However, a Dutch study that assessed subjects with pain showed that 39% of them sought specific information about this condition on the internet. 21 Similar to our study, the rate increased to 58% when subjects with internet access were evaluated as a subgroup. This high percentage of subjects seeking information about pain in The Netherlands might be related to the fact that 83% of the general population has internet access.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, a Dutch study that assessed subjects with pain showed that 39% of them sought specific information about this condition on the internet. 21 Similar to our study, the rate increased to 58% when subjects with internet access were evaluated as a subgroup. This high percentage of subjects seeking information about pain in The Netherlands might be related to the fact that 83% of the general population has internet access.…”
Section: Discussionsupporting
confidence: 72%
“…In a study conducted in England, 80% of the subjects preferred to receive their medical information directly from their physicians; only 19% searched for information on the internet. 21 Similarly, in a study conducted in The Netherlands, the subjects generally preferred to have their medical information provided by their physicians, despite having access to the internet. 5 Subjects in a study conducted in Taiwan stated that they did not seek medical information on the internet due to lack of time, lack of skill in accessing it, motivation, or even dissatisfaction with the information, considering it to be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet is likely to remain an unregulated resource through which anyone can provide or access information. The Internet has not only increased the possibility of patients accessing information intended for health care professionals, but may also put patients in a vulnerable position as they may encounter information which is unreliable, of poor quality, difficult to understand or may not even apply to their health care needs (Dolan et al, 2004).…”
Section: Advantages and Disadvantages Of E-health Informationmentioning
confidence: 99%
“…They observed a relationship between the frequency of Internet use and the short-term (communication) effects and long term (life benefits) effects on patients. Dolan et al (2004) sought to evaluate patients' use of the Internet information in a primary care setting. One of their results is that the use of online health related information makes most patients feel more prepared and able to participate in decision-making about treatments.…”
Section: Gender Differences In the Use Of Internet For Health Informamentioning
confidence: 99%
See 1 more Smart Citation